EFFECTS OF EXAMPLE-PROBLEM BASED LEARNING ON TRANSFER PERFORMANCE IN CIRCUIT THEORY - Jalani, Noor Hisham; Sern, Lai Chee (Journal of Technical Education and Training, 2014)
The main goal of the study was to test a hypothesis that Example-Problem-Based Learning (EPBL) would lead to better transfer performance compared Traditional Learning (TL) approach. The participants were vocational diploma-level students and the learning domain was Circuit Theory. As a means of data collection, 10-items open-ended test (five items each for assessing near-transfer and far-transfer) was administered as a pre-test and post-test. A sufficient reliability estimate was obtained, a= 0.74, based on the Cronbach Alpha method. A statistically significant difference on the post test score was observed between the EPBL and the TL group where the EPBL group scored higher than the TL group on both near and far-transfer. In conclusion, EPBL approaches produces greater learning compared to TL approach, for both near and distant-transfer.